Economic Consequences of Western Sanctions on Russia and the Evolution of Alternative Trade Networks - Mardan, Nawrs Sarhan; Al-Sharifi , Atard Awad; Al-Maamouri, Abdul Ali Kazim (Celebes Scholar pg, 2025)
The research looks into how Western sanctions influence the Russian Federation and what outcomes they have intended and unintended effects. The main effect of the sanctions is that Russia has had to scale back its economy, reduce GDP growth and lose connections with other countries. Yet, Russia has overcome these obstacles by dealing with non-Western countries, increasing its own production and further enforcing strong rule over its systems. Because of these sanctions, some countries are choosing to strengthen their cooperation with those willing to dodge the restrictions. The study points out that, along with these big economic shifts, business trading habits are starting to change, for example with more interest in decentralized and digital versions, as the isolated economy continues to develop. Although sanctions aim to slow down the Russian economy and make its leaders surrender, their lasting success is not clear, reflecting the complexity of world economic ties and Russia’s ability to change strategies over time.